Monsoon fasiculation paralysis syndrome: revisited - Pokalkar, Apeksha (International Journal of Research in Medical Sciences, 2025)
Cases of sudden onset external ophthalmoplegia with bulbar and skeletal muscle weakness and fasciculations are noted in this region during the monsoon season. The neurological deficit peaks within 2-3 days with potential risk of respiratory paralysis. Total recovery takes place recovery within 4-8 days if respiratory crises is taken care of. Two such cases who presented with acute onset of flaccid quadriplegia with relative preservation deep tendon jerks are reported here. There was no history of any bites or exposure to known toxins. The patients made spontaneous recovery in one week time.